Energy Consumption-poverty Reduction nexus in BRICS Nations - Tsaurai, Kunofiwa (International Journal of Energy Economics and Policy, 2021)
This study investigated the impact of energy consumption on poverty in BRICS using panel data analysis methods (fixed effects, pooled OLS, random effects, FMOLS) with annual data ranging from 1995 to 2018. Whether economic growth is a channel through which energy consumption influences poverty in BRICS was also a subject of investigation in this study? Although there is acknowledgment that energy consumption reduces poverty through economic growth by authors such as Okwanya et al (2015), Hussein and Filho (2012) and Okwanya and Abah (2018), there is no dedicated empirical study on the subject matter which exclusively focused on BRICS. Nothing is known about the energy consumption-growth-poverty nexus in BRICS, according to the author’s best knowledge. Also, majority of the energy consumption-poverty nexus empirical research wrongly assumed that the two variables (energy consumption and poverty) are linearly linked. Using both mean mortality rate and mean life expectancy as measures of poverty, the study noted that energy consumption reduced poverty in a significant way across all the four panel methods employed in BRICS. Economic growth was also generally found to have reduced poverty in BRICS countries. The complementarity between the two variables (energy consumption and poverty) had a significant poverty reduction effect in BRICS, in support of the existing literature. BRICS nations are therefore urged to develop and implement policies that ensure more energy consumption and increased economic growth activities if they intend to reduce poverty. Keywords: Energy Consumption; Growth; Poverty; BRICS; Panel data JEL Classifications: I32, Q43, O47 DOI: https://doi.org/10.32479/ijeep.11075